Fibroblast growth factor 2 promotes regeneration of cartilage by attracting mesenchymal stem cells to the site of cartilage injury - Khan, S; Muhammad, H; Scammahorn, J; Dell'Accio, F; Vincent, T (Elsevier, 2018)
An important response of cartilage to injury is release of fibroblast growth factor 2 (FGF2) from the pericellular matrix. Deletion of FGF2 in mice, leads to worsening cartilage degradation both spontaneously and after surgical induction of osteoarthritis (OA); thereby indicating a chondroprotective role for FGF2. One mechanism by which FGF2 could protect the joint is by promoting intrinsic repair after injury. Healing of focal cartilage defects in mice has been shown to be dependent upon background strain and age, with young DBA1 mice having superior regenerative capacity. It is presumed that repair is dependent upon mesenchymal stem cell (MSC) migration to the injured site, followed by the process of chondrogenesis. Here we test whether FGF2 is involved in these processes.